2020
DOI: 10.1108/jsma-07-2019-0120
|View full text |Cite
|
Sign up to set email alerts
|

Looking forward instead of backward

Abstract: PurposeAccording to behavioral research, aspirations influence a firm's search – exploitive and explorative – for solutions that satisfy a firm's goals. Yet, such goal seeking behavior is adaptive to a firm's past experiences and not to a manager's expectations of its firm's future. A manager's expectations are often explained in terms of their confidence in future events. The purpose of this study is to address the following research question: how does a manager's confidence influence its expectations of a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
(202 reference statements)
0
2
0
Order By: Relevance
“…In‐depth case studies could provide this (see also Bodwell & Chermack, 2010). This is particularly problematic because organizations can only become ambidextrous following the result of managerial decisions based on a strategic choice between different ambidexterity‐strategies (Ng, 2019). Thus, the research gap is to understand how the process of using corporate foresight in achieving ambidexterity is taking place and how that could be managed.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In‐depth case studies could provide this (see also Bodwell & Chermack, 2010). This is particularly problematic because organizations can only become ambidextrous following the result of managerial decisions based on a strategic choice between different ambidexterity‐strategies (Ng, 2019). Thus, the research gap is to understand how the process of using corporate foresight in achieving ambidexterity is taking place and how that could be managed.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Of these behaviors, innovation is given a higher priority in firms' search process. According to the theoretical model targeting the antecedents and outcomes of performance feedback established by Ng (2020), negative performance feedback can stimulate firms' exploitative and exploratory innovative behaviors. Based on the firm's motivation to undertake search behaviors, DasGupta and Mishra (2023) found that positive performance feedback positively impacts firm innovative search behaviors, whereas negative performance feedback positively influences its problem-driven search behaviors.…”
Section: Theory and Hypothesesmentioning
confidence: 99%